IN VITRO ANTIMALARIAL ACTIVITY OF CHLOROFORM, N-BUTANOL, AND ETHYL ACETATE FRACTIONS OF ETHANOL EXTRACTS OF CARTHAMUS TINCTORIUS LINN. FLOWERS - Hamsidi, Rini; Widyawaruyanti, Aty; Fuad Hafid, Achmad; Ekasari, Wiwied; Kasmawati, Henny; Akib, Nur Illiyyin; Wahyuni,; M, Hajrul Malaka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This objective of this research was to study in vitro antimalarial activity of chloroform, n-butanol, and ethyl acetate fractions of ethanol extracts of Carthamus tinctorius Linn. flowers from Asteraceae family which empirically been used as traditional medication by people in South Sulawesi to heal measles. Methods: Fractionation was conducted using chloroform, n-butanol, and ethyl acetate. Determination of antimalarial activity was performed by in vitro test using the 24-well microplate and the candle-jar method. Breeding is done in a petri-dish and done aseptically. Plasmodium falciparum 3D7 culture obtained from frozen deposits in-thawing and bread from Pharmacy Laboratory of Airlangga University, Surabaya, Indonesia. Blood sample with a density of over 2000 was employed. Serial decreasing concentrations of the crude extract of chloroform, butanol, and ethyl acetate fraction were tested for antimalarial activity. The following concentrations were used; 100; 10; 1.0; 0.1; and 0.01 (mg/mL). Negative controls used dimethyl sulfoxide (DMSO) diluted in the same manner as diluting materials above test, to obtain final DMSO concentration is not more than 0.5%. Mixture and suspension test parasites (= test preparation) are then inserted into the candle-jar and incubated in a CO2 incubator at a temperature of 37Â°C for 48 h. After incubation for 48 h made a thin blood smear on glass object. Smear dried at room temperature, fixed with methanol, then, once dry stained with Giemsa and counted under a microscope parasitemianya with 1000 times magnification. Calculations performed on 5000's erythrocytes. Results: Results showed that chloroform and n-butanol fraction cannot inhibit parasitemia >50%, but ethyl acetate fraction can inhibit parasitemia >50% with the highest inhibition at 100 Î¼g/mL of 94.48%. Conclusion: Ethyl acetate fraction is highly active as antimalarial with an IC50 of 1.25 Î¼g/mL.